The Acute vs Chronic Post-CABG Complications: Does Gender Matter? A Retrospective Cohort Study from the Jordan University Hospital Records - Abu hantash, Noor; Abu Shirbi, Shahed; Natheer, Dyala; Yasin, Jehad; Al-Makhamreh, Elia; Rabah, Reham; Maaita, Farhan; Al-Smady, Moaath; Al-Makhamreh, Hanna (Jordan Medical Journal, 2025)
Background: This study aimed to examine coronary artery bypass grafting (CABG) and its acute and chronic postoperative complications at Jordan University Hospital (JUH). Methods: JUH’s electronic health records (EHR) and surgery databases of 238 patients were reviewed from 1st January 2010 to 5th July 2024, regarding their relation to gender, techniques used in the surgery, and postoperative complications of CABG. Results: The study cohort included 238 patients undergoing CABG, comprising 52 females (21.85%) and 186 males (78.15%). Postoperative complications were analyzed by gender. Among females, 17.31% (9/52) experienced complications, while 82.69% (43/52) had none. In males, 10.22% (19/186) exhibited complications, and 89.78% (167/186) were complication-free, yielding a total of 210 patients (210/238, 88.24%) without complications. Chi-square analysis revealed no significant association between gender and complication incidence (χ²=1.35, p=0.246). Complications were further stratified into acute and chronic categories. Females demonstrated the following: 9.62% (5/52) with acute complications (e.g., nosocomial infection), 3.85% (2/52) with concurrent acute and chronic complications (e.g., nosocomial infection and cataract), and 3.85% (2/52) with chronic complications (e.g., cataract). Among males, 3.76% (7/186) presented with acute complications, 0.54% (1/186) with both acute and chronic complications, and 5.91% (11/186) with chronic complications. A Chi-square test evaluating gender-based differences in acute versus chronic complication susceptibility showed no significant association (χ²=6.84, p=0.077; Monte Carlo p=0.425), with Monte Carlo simulation applied due to low expected cell frequencies. These findings suggest no statistically significant relationship between gender and the development of post-CABG complications, either in overall incidence or subtype (acute vs chronic). Conclusion: Descriptive statistics showed that females had a higher incidence of complications than males overall and acutely, while males tend to develop their complications chronically. However, there is no significant association between gender and complications, either the total complications or the subclassified ones.